Implikasi politik Melayuisme Sama-Bajau di Malaysia - Gusni Saat, (Universiti Kebangsaan Malaysia, 2008)
This paper discusses political implications of Sama-Bajau’s Malayism in Malaysia. Sama-Bajau in Sabah claim that they came from Johor. This means ethnically and ideologically they are Malays. Whenever they encounter any local conflict, such as identity and political conflicts, a Sama-Bajau will look to the Malay culture for source of strength. This process is referred to as Malayism of the Sama-Bajaus. The argument of this paper is that the source of Malay political consolidation in Sabah is the Malayism of the Sama-Bajau and other Muslim indigenous peoples